In and out of Suriname : language, mobility and identity - Carlin, Eithne; Léglise, Isabelle; Migge, Bettina; Tjon Sie Fat, Paul Brendan (Caribbean series (Koninklijk Instituut voor Taal-, Land- en Volkenkunde (Netherlands)), 2014)
This title is available online in its entirety in Open Access In and Out of Suriname: Language, Mobility and Identity offers a fresh multidisciplinary approach to multilingual Surinamese society, that breaks through the notion of bounded ethnicity enshrined in historical and ethnographic literature on Suriname.